LINGUOCULTURAL FEATURES OF THE REALIZATION OF THE CONCEPT OF “GREETING” IN ENGLISH, UZBEK, AND RUSSIAN PAREMIOLOGICAL TEXTS - Khushmanova Shakhnoza Ibragimovna (Bright Mind Publishing, 2025)
This study investigates the linguocultural features of the concept of “greeting” as it is realized in the paremiological (proverbial) texts of English, Uzbek, and Russian languages. Paremiology provides a unique lens to explore how culture, social values, and linguistic norms shape the expression and function of greetings across different societies. Through a comparative analysis of selected proverbs and sayings, this article reveals the underlying cultural ideologies, communication patterns, and social expectations encoded within greeting-related paremia. The findings demonstrate distinct national-cultural traits manifested in language usage, metaphorical expressions, and pragmatic functions, thereby contributing to the fields of intercultural communication, cognitive linguistics, and folklore studies.
Keywords: Greeting, paremiology, linguocultural features, English proverbs, Uzbek proverbs, Russian proverbs, intercultural communication